Alun Samudra Rasa, a Javanese Novels by Ardini Pangastuti Bn - Winarsih (Abjad Journal of Humanities & Education, 2024)
Alun Samudra Rasa is a Javanese novel by Ardini Pangastuti Bn, a writer of modern Javanese literature. The novel tells the story of a woman who is a housewife and career woman who experiences misfortune in marriage, so she continues to fight for her self-esteem and struggles with the inner conflicts that affect her. Alun Samudra Rasa has its uniqueness compared to other fictional literary works; the author gives it a new colour by displaying geguritan shapes in each chapter in the book, which already describes the whole story because each part of the geguritan shown summarises the story in that chapter. Pangastuti created Alun Samudra Rasa with unique language and an aesthetic impression. Intan is a career woman and mother of one daughter. He experienced poor living conditions at home. Intan's suffering began when the couple's busy schedule led to less harmonious communication. Bregas, Intan's husband, thinks that Intan lowers her self-esteem because she has more income and achievements than Bregas. Jealousy and suspicion arise in self Bregas. His mounting emotions had made him dare to commit domestic violence against his wife, which resulted in drinking and infidelity. The conflict escalated when Intan returned to her parents' house. They finally could not maintain their marriage anymore. A life built based on an accident is not always smooth; Intan is forced to Marry Bregas Because she was pregnant at that time. Amid Intan's troubled heart facing the trials of her marriage, she is reunited with her ex-boyfriend, who has built his small family. Intan's desire to rise from adversity to become an independent and successful woman makes her close to her ex-lover. This closeness was a mistake that caused Intan to deal with her ex-lover's wife. What Intan   fears most about her closeness to Pram is when Pram's wife finds out. Lousy day, of course. No. On the calendar, Pram's wife came and attacked Intan and even cursed at her. Intan felt she had no self-esteem and only pondered the conflict within her heart. Alun Samudra Rasa contains the story of a woman's struggle to face the twists and turns of her domestic life. Forms of problems in domestic life that realistically also occur in society. Intan teaches persistence and struggle to rise from the problems they face. He also provides a picture of domestic life that makes readers consider being careful when choosing a partner. The expressions of the words inscribed in Alun Samudra Rasa contain meaning and variations in the freshness of the language with the choice of aesthetic diction, thus pleasing the reader's eyes and soul. Intan invites the reader to feel her suffering and be trapped in the inner conflict she is experiencing. This novel also provides interest at the end of the story. Readers will definitely be curious about what will happen to Intan after chatting with her mind and thoughts. Also, most readers do not realise that chapter 31 does not start with a groan like the previous chapters. However, the answer is found at the end of the story. The reader is surprised at the end of the story when a speech containing Irene's feelings plays in her mind. When reading the statement describing Intan's feelings, the reader will understand why this novel uses the title Alun Samudra Rasa. The end of the story leads the reader to speculate on the results of Intan's quiet contemplation and her hopes for moving forward. Intan tells about the wounds in her life that have occurred to the reflection of the beautiful life that she has not yet lived. Through expressing Intan's feelings of loneliness, the reader develops thoughts to describe Intan's life after going through this sad life event. Alun Samudra Rasa is an aesthetic novel with high artistic value. This novel is also used as a didactic tool by the author. Young couples about to step into married life are very suitable to read this novel as a mirror of life that describes the hustle and bustle of problems in the household and reminds them to be careful in choosing a life partner. This novel, which also has a feminist genre, teaches women to be able to stand on their own feet—fighting for women's rights so that they are not underestimated and receive arbitrary treatment from men. A woman must also be able to maintain her dignity. Indirectly, the novel explains that Intan made a wrong move because she did not maintain her dignity and ended up trapped in a full-fledged marriage, suffering with Bregas. A man who is jealous, possessive, rude, angry, drunk, and even likes playing with women. Characteristic features Bregas can make as a benchmark to avoid when choosing a partner. Apart from that, this novel also includes scenes where parents are too busy to lack closeness with their children. Intan, a career woman who spends much time in the office, has less time with her children. He even gave complete trust to his caregiver. I want to convey the importance of closeness between children and parents. Intan also realised this when she met her friend, who was so concerned and did not want to miss out on her child's golden age that she put aside her ego and desires. So, this novel teaches parents about parenting patterns. This novel is generally easy to understand because it uses modern Javanese language. However, the author also includes expressions from Indonesian, English, and foreign languages, as well as abbreviations and slang expressions. However, there is a form of carelessness in writing novels, so on one page, there are words that are wrong and become forms of other words that are less polite. However, apart from these mistakes, this novel is indeed excellent. Through the language used, it can be seen that this novel has weight. The author does not forget to use dictions in Javanese such as tembung entar, sign (pralambang), synonyms, figures of speech such as hyperbole and personification, and various forms of reduplication which are continuously repeated in several parts which create uniqueness. Moreover, the novel's content depicts life that often occurs and is found in society to be used as a mirror and lesson for readers. It can be concluded that Alun Samudra Rasa asks us to prepare well beforehand to step into married life and reduce excessive expectations in marriage before finally feeling disappointed, regretful, and trapped in suffering that ends in divorce.